(untitled) (Journal of Economic Research & Business Administration, 2016)
The current state of the consumer market is characterized by the in- crease in activity and an increase in customers’ requirements for qual- ity products and services, as well as a high rate of change in consumer preferences and the situation in general. In order to respond adequately to changes and remain competitive, companies must have effective and quality management system and marketing. Currently, Kazakhstan perfum- ery and cosmetics market takes care of the trading in the public markets, where products are sold mainly the mass market. This indicates the transi- tion to a civilized level of retail sales, close to European standards. In this regard, this paper examines the current market situation, problems and proposed solutions.